AN ANALYSIS OF FEMINISM IN HOW TO BE SINGLE MOVIE DIRECTED BY CHRISTIAN DITTER - dewi, tati mar; Zamil, Cholijah; Indriyani, Furi (English Education:Journal of English Teaching and Research, 2018)
The purpose of this analysis is to know what the meaning of feminism, each type of feminism, and the benefits of feminism in everyday life. Feminism is womens’ movement that demands justice and equal rights with men. Feminism is divided into liberal feminism, postmodern feminism, radical feminism, socialist marxist feminism, and anarchist feminism. Movie How to be Single is perfect for analyzing feminism, as it tells about the lives of women who try to keep themselves. Some scenes in the movie contain feminism. As seen in modern times many women work and fulfill their own lives. After doing some processes of observation from many opinions of experts, journals, books, social media, feminism is a collection of women who want to have the same rights as men. Feminism and its types can be used to protect women from violence that may occur in everyday life. So women have the right and justice for themselves. To be feminism is not dangerous or embarrassing if we look from a positive angle. Keywords: Analysis, Feminism, Types of Feminism